(untitled) (Canadian Dermatology Today, 2024)
The use of biosimilars is becoming standard practice for Canadian dermatologists. However, most of these clinicians most likely graduated prior to their adoption of biosimilars and, as a result, are likely to have minimal to no experience with biosimilars. Considering this limited prior experience, it can be challenging to gain a full understanding of how one biosimilar differentiates from another. The objective of this paper is to educate clinicians so that they are well‑informed on how to select the appropriate biosimilar for the patient at hand. This literature review and summary will review the current biosimilar landscape in Canada; review nuances between adalimumab biosimilars; and review available clinical experience data of adalimumab switch to biosimilar and vice versa for the treatment of hidradenitis suppurativa (HS). It also aims to highlight methodologies for improving biosimilar patient compliance when switching to alternative agents.